2021
DOI: 10.1080/00223131.2020.1862718
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of core material energy change during the in-vessel phase of Fukushima Daiichi Unit 3 based on observed pressure data utilizing GOTHIC code analysis

Abstract: The vapor formation within the reactor pressure vessel (RPV) is regarded to represent heat removal from core materials to the coolant, while the hydrogen generation within the RPV is regarded to represent heat generation by metal oxidation. Based on this understanding, the history of the vapor/hydrogen generation in the in-vessel phase of Fukushima Daiichi Nuclear Power Station Unit 3 was evaluated based on the comparison of the observed pressure data and the GOTHIC code analysis results. The resultant vapor/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This observation shows that there are flow paths at the lower head of the RPV on one hand. On the other hand, the former study (Sato, et al, 2021a) suggested that some of the SRVs would have had significant leakage to the D/W during the accident progression phase. These two flow paths are believed to have been effective during the debris cooling phase studied here.…”
Section: Analysis Of Unit 3 Temperature Data (Tepco 2012b)mentioning
confidence: 93%
See 2 more Smart Citations
“…This observation shows that there are flow paths at the lower head of the RPV on one hand. On the other hand, the former study (Sato, et al, 2021a) suggested that some of the SRVs would have had significant leakage to the D/W during the accident progression phase. These two flow paths are believed to have been effective during the debris cooling phase studied here.…”
Section: Analysis Of Unit 3 Temperature Data (Tepco 2012b)mentioning
confidence: 93%
“…It was finally followed by the temperature decrease down to the saturation and the debris was inundated by liquid water as can be observed presently. It is estimated (Sato, et al, 2021a) that the "vent-clear condition", i.e., D/W pressurization resulting in total clearance of liquid water in the S/C vent pipe, was established just after 9:00 of March 13th when the operation of the Automatic Reactor Depressurization System (ADS) took place. This vent-clear condition lasted until 20:40 of March 13th.…”
Section: Overview On the Two-week-long Debris Cooling Behaviormentioning
confidence: 99%
See 1 more Smart Citation